Bonding wire for semiconductor devices
By adding specific alloy elements and layer structures to the Cu bonding wire, the corrosion and reliability problems of Cu bonding wire in high temperature and high humidity environment are solved, and the reliability and density of the ball joints in high temperature environments above 175°C are achieved. Improved compatibility.
Patent Information
- Application Number
- CN201780097315.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2017-12-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2037-12-28
AI Technical Summary
In high temperature and high humidity environment, the bonding reliability of the ball joint part of the Cu bonding wire cannot meet the requirements of 175°C or above. Especially in molding resins using sulfur-containing silane coupling agents, Cu corrosion problems are serious, resulting in bonding Reduced reliability.
Using Pd coated Cu bonding wire, adding alloy elements such as Ni, Rh, and Ir to form Pd coated layer and Au-Pd alloy skin layer, and adding elements such as Li, Sb, and Fe to the Cu alloy core material to control the content of alloy elements. and layer thickness to improve yield strength and oxidation resistance of the bonding wire, and inhibit diffusion and corrosion of Cu and Al.
Under a high temperature environment above 175°C, the bonding reliability and adhesion of the ball joint are significantly improved, the bonding life is extended, the corrosion of Cu and the FAB shape shift are reduced, and the shape roundness of the ball joint is improved. and wedge engagement.
Smart Images

Figure BDA0002515071910000191 
Figure BDA0002515071910000201 
Figure BDA0002515071910000211
Abstract
Description
Technical Field
[0001] The present invention relates to a bonding wire for a semiconductor device for connecting an electrode on a semiconductor element to a wiring on a circuit wiring board such as an external lead. Background Art
[0002] At present, as a bonding wire for semiconductor devices (hereinafter referred to as "bonding wire") for bonding electrodes on semiconductor elements and external leads, thin wires with a wire diameter of about 15 to 50 μm are mainly used. The bonding method of bonding wires is generally a thermal compression method using ultrasonic waves, and a general bonding device, a wedge jig for connecting by passing the bonding wire through its interior, etc. can be used. In the bonding process of the bonding wire, after the wire tip is heated and melted by arc heat energy and a ball (FAB: Free Air Ball) is formed by surface tension, the ball is pressed and bonded to the electrode of the semiconductor element heated in the range of 150 to 300°C (hereinafter referred to as "ball bonding"), and then after the wire arc is formed, the wire part is pressed and bonded to the electrode on the external lead side (hereinafter referred to as "wedge bonding"), and the bonding process of the bonding wire is completed. The electrode on the semiconductor element to which the bonding wire is bonded uses an electrode structure in which an alloy mainly composed of Al is formed on a Si substrate, and the electrode on the external lead side uses an electrode structure plated with Ag or Pd.
[0003] Until now, Au has been the mainstream material for bonding wires, but substitution with Cu is progressing, mainly for LSI applications. On the other hand, with the popularity of electric vehicles and hybrid vehicles in recent years, there is also an increasing demand for substitution from Au to Cu in vehicle-mounted equipment applications.
[0004] For Cu bonding wire, a scheme of using high-purity Cu (purity: 99.99 mass % or more) has been proposed (for example, Patent Document 1). Cu has the disadvantage of being easily oxidized compared to Au, and has problems such as poor bonding reliability, ball forming properties, and wedge bonding properties. As a method for preventing surface oxidation of Cu bonding wire, a structure in which the surface of the Cu core material is coated with a metal such as Au, Ag, Pt, Pd, Ni, Co, Cr, and Ti has been proposed (Patent Document 2). In addition, a structure in which the surface of the Cu core material is coated with Pd and its surface is coated with Au, Ag, Cu, or an alloy thereof has been proposed (Patent Document 3).
[0005] Compared with general electronic instruments, vehicle-mounted equipment requires higher bonding reliability in harsh high-temperature and high-humidity environments. In particular, the bonding life of the ball joint that connects the ball part of the wire to the electrode is the biggest problem. Several methods for evaluating bonding reliability in high-temperature and high-humidity environments have been proposed. A representative evaluation method is HAST (Highly Accelerated Temperature and Humidity Stress Test). When evaluating the bonding reliability of the ball joint by HAST, the ball joint used for evaluation is exposed to a high-temperature and high-humidity environment with a temperature of 130°C and a relative humidity of 85%. The bonding life of the ball joint is evaluated by measuring the change in the resistance value of the joint over time, or measuring the change in the shear strength of the ball joint over time. Recently, a bonding life of more than 100 hours has been required in HAST under such conditions. In the molding resin (epoxy resin) used as the package of the semiconductor device, the molecular skeleton contains chlorine (Cl). Under the HAST evaluation conditions, the Cl in the molecular skeleton is hydrolyzed and dissolved as chloride ions (Cl-). Even if the Cu bonding wire has a Pd coating layer, when it is bonded to the Al electrode by ball bonding, if the Cu / Al bonding interface is placed at a high temperature of 130°C or higher, Cu9Al4 as an intermetallic compound is formed, and Cl eluted from the molding resin causes corrosion to progress, resulting in a decrease in bonding reliability.
[0006] Patent documents 4 to 8 disclose an invention in which the corrosion reaction is delayed and the bonding reliability in a high temperature and high humidity environment is improved by making the Pd-coated Cu wire contain one or more elements selected from the group consisting of Ni, Pd, Pt, In, As, Te, Sn, Sb, Bi, Se, Ga, and Ge.
[0007] In recent years, in automotive semiconductor devices, there is a demand for improved bonding reliability of ball joints at 175°C to 200°C. The packaging of the semiconductor device, i.e., the molding resin (epoxy resin), contains a silane coupling agent. In the case of automotive semiconductors that require reliability at higher temperatures and require high adhesion, "sulfur-containing silane coupling agents" are added. The sulfur contained in the molding resin is freed under conditions above 175°C (for example, 175°C to 200°C). If the free sulfur comes into contact with Cu, the corrosion of Cu becomes severe. If Cu corrosion occurs in a semiconductor device using a Cu bonding wire, the bonding reliability of the ball joint, in particular, is reduced.
[0008] Even when a sulfur-containing silane coupling agent is used in a molding resin for semiconductor device packaging, it is required to ensure the bonding reliability of the ball joint in a high temperature environment of 175°C or above. To achieve this purpose, an invention is disclosed in which the Cu core material of the Pd-coated Cu bonding wire contains various alloy elements. Patent documents 6 to 9 disclose that by containing a predetermined amount of one or more elements selected from the group consisting of Pt, Pd, Rh, Ni, As, Te, Sn, Sb, Bi, Se, Ni, Ir, Zn, Rh, and In in the Pd-coated Cu wire, the bonding reliability of the ball joint in a high temperature environment of 175°C or above can be improved.
[0009] The invention discloses that, when ball bonding is performed using a Pd-coated Cu bonding wire, a trace amount of an element is contained in the Pd-coated Cu bonding wire in order to achieve a good spherical shape and to improve the crush shape of the ball bonding portion to improve the roundness of the ball bonding portion. Patent documents 4 to 9 disclose that a good spherical shape is achieved or the crush shape of the ball bonding portion is improved by containing 0.0001 to 0.01 mass % (1 to 100 mass ppm) of one or more elements selected from the group consisting of P, B, Be, Fe, Mg, Ti, Zn, Ag, Si, Ga, Ge, Ca, and La in the wire.
[0010] [Prior art literature]
[0011] [Patent Document]
[0012] Patent Document 1: Japanese Patent Application Laid-Open No. 61-48543
[0013] Patent Document 2: Japanese Patent Application Publication No. 2005-167020
[0014] Patent Document 3: Japanese Patent Application Publication No. 2012-36490
[0015] Patent Document 4: Japanese Patent No. 5893230
[0016] Patent Document 5: Japanese Patent No. 5964534
[0017] Patent Document 6: Japanese Patent No. 5912005
[0018] Patent Document 7: Japanese Patent No. 5937770
[0019] Patent Document 8: Japanese Patent No. 6002337
[0020] Patent Document 9: Japanese Patent No. 5912008 Summary of the invention
[0021] [Problems to be solved by the invention]
[0022] As described above, even when a sulfur-containing silane coupling agent is used in a molding resin for semiconductor device packaging, the bonding reliability of the ball bond can be improved in a high temperature environment of 175° C. or higher by incorporating various alloy elements into the Cu core material of the Pd-coated Cu bonding wire.
[0023] On the other hand, the sulfur content in the molding resin has tended to increase in recent years. In the past, commercially available epoxy resins containing sulfur-containing silane coupling agents were used. In order to improve the adhesion of the bonding wire to the lead frame and the semiconductor chip, thereby improving the reflow resistance, the sulfur content in the recent epoxy resins has increased compared to the past. The present inventors have found that if such an epoxy resin with an increased sulfur content is used as a molding resin for semiconductor device packaging, even when the inventions described in patent documents 6 to 9 are used, the bonding reliability of the ball joint may not be fully obtained in a high temperature environment of 175°C or above.
[0024] The present invention is directed to a Pd-coated Cu bonding wire and aims to provide a bonding wire for a semiconductor device, wherein even when the sulfur content in a molding resin used for semiconductor device packaging is increased, sufficient bonding reliability of a ball bonding portion can be obtained in a high temperature environment of 175°C or above.
[0025] [Technical solutions for solving technical problems]
[0026] That is, the gist of the present invention is as follows.
[0027] (1) A bonding wire for a semiconductor device, comprising a Cu alloy core material and a Pd coating layer formed on a surface of the Cu alloy core material, wherein:
[0028] The bonding wire contains one or more of Ni, Rh, and Ir (hereinafter referred to as "the first alloy element group") and one or both of Pd: 0.05 mass % or more (hereinafter referred to as "the first + alloy element group"), and when the content of the first alloy element group is evaluated as the content in the bonding wire, and the Pd content is evaluated by converting the content of the first alloy element group into the content in the bonding wire based on the Pd content in the Cu alloy core material, the total content of the first alloy element group and Pd in the evaluated content is 0.03 to 2 mass %;
[0029] The bonding wire further contains a total of 0.002 to 3 mass % of one or more of Li, Sb, Fe, Cr, Co, Zn, Ca, Mg, Pt, Sc, and Y (hereinafter referred to as the "second alloy element group"). When Ca and Mg are contained, the contents of Ca and Mg in the bonding wire are respectively 0.011 mass % or more. When Zn is contained, the total content of the first alloy element group and Zn is 2.1 mass % or more.
[0030] (2) The bonding wire for a semiconductor device according to (1), wherein the thickness of the Pd coating layer is 0.015 to 0.150 μm.
[0031] (3) The bonding wire for a semiconductor device according to (1) or (2), further comprising an alloy skin layer containing Au and Pd on the Pd coating layer.
[0032] (4) The bonding wire for a semiconductor device according to (3), wherein the thickness of the alloy skin layer containing Au and Pd is 0.050 μm or less.
[0033] (5) The bonding wire for a semiconductor device according to any one of (1) to (4), further comprising a total of 0.03 to 3 mass % of one or more of Al, Ga, Ge, and In (hereinafter referred to as the "third alloy element group").
[0034] (6) A bonding wire for a semiconductor device as described in any one of (1) to (5), characterized in that the bonding wire further contains a total of 0.1 to 1000 mass ppm (Sn≦10 mass ppm, Bi≦1 mass ppm) of one or more of As, Te, Sn, Bi, and Se (hereinafter referred to as the "fourth alloy element group").
[0035] (7) The bonding wire for a semiconductor device according to any one of (1) to (6), further comprising a total of 0.1 to 200 mass ppm of one or more of B, P, and La (hereinafter referred to as the "fifth alloy element group").
[0036] (8) The bonding wire for a semiconductor device according to any one of (1) to (7), wherein Cu exists on the outermost surface of the bonding wire.
[0037] Effects of the Invention
[0038] According to the present invention, it is possible to provide a semiconductor device bonding wire which can obtain sufficient bonding reliability of a ball joint even in a high temperature environment of 175° C. or higher even when the sulfur content in a molding resin used for semiconductor device packaging is increased. DETAILED DESCRIPTION
[0039] Hereinafter, the present invention will be described in detail based on preferred embodiments. Hereinafter, the numerical values shown in relation to the content, thickness, and ratio represent average values unless otherwise specified.
[0040] The bonding wire of the present invention has a Cu alloy core material and a Pd coating layer formed on the surface of the Cu alloy core material. If such a Pd-coated Cu bonding wire is used to form a ball by arc discharge, an alloy layer with a higher Pd concentration than the inside of the ball is formed on the surface of the ball during the process of melting and solidification of the bonding wire. If the ball is bonded to an Al electrode and a high temperature and high humidity test is performed, Pd becomes enriched at the bonding interface. The enriched layer formed by the Pd enrichment can inhibit the diffusion of Cu and Al at the bonding interface in the high temperature and high humidity test, and reduce the growth rate of easily corrosive compounds. Therefore, the Pd-coated Cu bonding wire of the present invention can improve the bonding reliability. In addition, because the alloy layer with a high Pd concentration formed on the surface of the ball has excellent oxidation resistance, it is possible to reduce defects such as the deviation of the formation position of the ball relative to the center of the bonding wire when the ball is formed.
[0041] In recent years, in semiconductor devices for vehicles, it is required to improve the bonding reliability of ball joints at 175°C to 200°C. As mentioned above, the packaging of semiconductor devices, that is, the molding resin (epoxy resin), contains a silane coupling agent. Since the silane coupling agent has the function of improving the adhesion between organic matter (resin) and inorganic matter (silicon or metal), it can improve the adhesion with the silicon substrate or metal. Furthermore, in the case of high adhesion required for semiconductor devices for vehicles that require reliability at higher temperatures, "sulfur-containing silane coupling agents" are added. The sulfur contained in the molding resin will be freed if used under conditions above 175°C (for example, 175°C to 200°C). In addition, if the free sulfur at a high temperature above 175°C comes into contact with Cu, the Cu corrosion becomes severe, and sulfide (Cu2S) and oxide (CuO) are generated. If Cu corrosion is generated in a semiconductor device using a Cu bonding wire, the bonding reliability of the ball joint is reduced in particular.
[0042] As a method for evaluating the bonding reliability of ball joints in a high temperature environment above 175°C, HTS (High Temperature Storage Test) is used. For evaluation samples exposed to a high temperature environment, the bonding life of the ball joints is evaluated by measuring the change in the resistance value of the ball joints over time or the change in the shear strength of the ball joints over time.
[0043] In the bonding wire for semiconductor devices of the present invention having a Cu alloy core material and a Pd coating layer formed on the surface of the Cu alloy core material, the bonding wire contains one or more of Ni, Rh, and Ir (hereinafter referred to as the "first alloy element group") and Pd: 0.05 mass % or more of one or both. The content of the first alloy element group is evaluated as the content in the bonding wire. The Pd content is evaluated by converting the Pd content in the Cu alloy core material into the content in the bonding wire. That is, the Pd content can be calculated by analyzing the Pd content in the Cu alloy core material and multiplying the analyzed value by "(the mass of the Cu alloy core material per unit length of the wire) / (the mass of the bonding wire per unit length of the wire)". The Pd in the Pd coating layer is not added to the Pd content. The present invention is characterized in that, in the content evaluated in this way, the total content of the first alloy element group and Pd is 0.03 to 2 mass %. If the sulfur content in the molding resin used in semiconductor device packaging is the same as that of the previous molding resin containing a sulfur-containing silane coupling agent, by containing one or both of the first alloy element group and Pd (hereinafter referred to as the "first + alloy element group") within the above-mentioned content range, the bonding reliability of the ball joint in a high-temperature environment above 175°C can be improved. This is as described in the above-mentioned patent documents 6 to 9. Furthermore, by containing the first + alloy element group within the above-mentioned range, the wire arc formability can be improved, that is, the inclination that becomes a problem in high-density mounting can be reduced. This is because the yield strength of the bonding wire is improved by containing these elements, and the deformation of the bonding wire can be suppressed.
[0044] In addition, by containing the first + alloy element group within the above content range, the bonding life of the ball joint in a high temperature and high humidity environment of 130°C and a relative humidity of 85% can also be improved. If the Pd-coated Cu bonding wire contains the first + alloy element group as in the present invention, it can be considered that there is a tendency to suppress the formation of Cu9Al4 intermetallic compounds in the bonding part. If these elements are added, the interfacial tension between the Cu of the core material and the Pd of the coating layer is reduced, and Pd enrichment of the ball bonding interface occurs effectively. Therefore, the mutual diffusion inhibition effect of Cu and Al brought by the Pd-enriched layer becomes stronger, and as a result, the amount of Cu9Al4 that is easily corroded under the action of Cl is reduced, which can be inferred to improve the reliability of the ball joint in a high temperature and high humidity environment.
[0045] The lower limit of the content of the first + alloying element group consisting of Ni, Rh, Ir, and Pd is as described above, and the total amount in the bonding wire is 0.03 mass%. More preferably, the lower limit of the content is 0.05 mass% or more, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, or 0.5 mass% or more. In the case of containing Pd, the lower limit of the Pd content is 0.05 mass%. More preferably, the lower limit of the Pd content is 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, or 0.5 mass% or more. On the other hand, the upper limit of the content of the first + alloying element group is as described above, which is 2 mass%. This is because if the content of the first + alloying element group exceeds 2 mass%, FAB hardening is easy to cause chip cracks during line bonding. More preferably, the upper limit of the content is 1.8 mass% or less, or 1.6 mass% or less.
[0046] On the other hand, if the sulfur content in the molding resin increases, when only the first alloy element group is contained as described above, the bonding reliability of the ball joint may not be sufficiently obtained in a high temperature environment of 175°C. In the present invention, this problem can be solved by including one or more of Li, Sb, Fe, Cr, Co, Zn, Ca, Mg, Pt, Sc, and Y (the second alloy element group) in the bonding wire in addition to the first alloy element group. When the first alloy element group and the second alloy element group are contained at the same time, in addition to achieving the effect of the first alloy element group, that is, suppressing the tendency of the formation of Cu9Al4 intermetallic compounds that are easily corroded by sulfur in the joint, by containing the second alloy element group, when the sulfur released from the sealing resin acts on the Cu9Al4 of the joint and the corrosion progresses, the second alloy element group captures the sulfur (compounds it) and makes it harmless. Therefore, even if Cu9Al4 is generated, the bonding strength after HTS can be maintained by suppressing the development of corrosion. The total content of the second alloying element group is more preferably 0.005 mass % or more, and further preferably 0.02 mass %, 0.05 mass %, 0.1 mass %, 0.2 mass %, 0.3 mass %, or 0.5 mass %. In addition, in the second alloying element group, with respect to Ca and Mg, since it is confirmed that the above-mentioned effect is exerted when their content is 0.011 mass % or more, the lower limits of the contents of Ca and Mg are respectively determined to be 0.011 mass % when Ca and Mg are contained. That is, when the bonding wire contains Ca, the content of Ca in the bonding wire is 0.011 mass % or more, and when the bonding wire contains Mg, the content of Mg in the bonding wire is 0.011 mass % or more. The lower limits of the contents of Ca and Mg are respectively preferably 0.015 mass %, 0.02 mass %, 0.03 mass %, 0.05 mass %, 0.1 mass %, 0.2 mass %, or 0.3 mass %. On the other hand, the total content of the second alloying element group is less than 3% by mass. If the total content of the second alloying element group exceeds 3% by mass, FAB hardening and chip cracks are easily caused during online bonding. The content of the second alloying element group is more preferably less than 2.5% by mass, less than 2% by mass, less than 1.8% by mass, or less than 1.6% by mass. In addition, when Zn is contained as the second alloying element group, the above effect is obtained when the total content of the first alloying element group and Zn is more than 2.1% by mass, and the development of corrosion can be further suppressed by increasing the capture effect of sulfur. It is more preferred if the total content of the first alloying element group and Zn is more than 2.5% by mass, and further preferably more than 3.0% by mass, more than 3.5% by mass.
[0047] In one embodiment, the bonding wire of the present invention must contain at least one of Sc and Y as the second alloy element group. In this embodiment, the bonding wire of the present invention contains at least one of Sc and Y, and the total content of the second alloy element group consisting of Li, Sb, Fe, Cr, Co, Zn, Ca, Mg, Pt, Sc, and Y is 0.002 to 3 mass%. The total content of the second alloy element group, the lower limit of the content of Ca and Mg, and the preferred range of the total content of the first alloy element group and Zn when Zn is included are as described above, but the content of at least one of Sc and Y, that is, the total content of Sc and Y is preferably 0.002 mass% or more, 0.005 mass% or more, 0.02 mass% or more, 0.05 mass% or more, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, or 0.5 mass% or more. In addition, in this embodiment, the total content of Sc and Y is preferably 2.5 mass% or less, 2 mass% or less, 1.8 mass% or less, or 1.6 mass% or less.
[0048] In the bonding wire of the present invention, from the viewpoint of further improving the bonding reliability of the ball joint under the high temperature and high humidity environment required for vehicle-mounted equipment and from the viewpoint of suppressing the eccentricity of the FAB to obtain a better FAB shape, the thickness of the Pd coating layer is preferably 0.015 μm or more, more preferably 0.02 μm or more, and further preferably 0.025 μm or more, 0.03 μm or more, 0.035 μm or more, 0.04 μm or more, 0.045 μm or more, or 0.05 μm or more. On the other hand, from the viewpoint of suppressing the shrinkage cavity of the FAB to obtain a better FAB shape, the thickness of the Pd coating layer is preferably 0.150 μm or less, more preferably 0.140 μm or less, 0.130 μm or less, 0.120 μm or less, 0.110 μm or less, or 0.100 μm or less.
[0049] The definitions of the Cu alloy core and the Pd coating layer of the above-mentioned bonding wire are explained. The boundary between the Cu alloy core and the Pd coating layer is determined based on the Pd concentration. Taking the position where the Pd concentration is 50 atomic % as the boundary, the area with a Pd concentration of 50 atomic % or more is determined as the Pd coating layer, and the area with a Pd concentration of less than 50 atomic % is determined as the Cu alloy core. The reason for this is that if the Pd concentration in the Pd coating layer is 50 atomic % or more, the structure of the Pd coating layer will achieve an improvement in characteristics. The Pd coating layer may also include an area where Pd is alone, and an area where Pd and Cu have a concentration gradient in the depth direction of the wire. The reason for forming an area with this concentration gradient in the Pd coating layer is that sometimes the heat treatment in the manufacturing process causes the diffusion of Pd and Cu atoms. In the present invention, the concentration gradient refers to a concentration change in the depth direction of 10 mol % or more per 0.1 μm. Furthermore, the Pd coating layer may also contain unavoidable impurities.
[0050] The bonding wire of the present invention may further include an alloy skin layer containing Au and Pd on the Pd coating layer. Thus, the bonding wire of the present invention can further improve wedge bonding properties.
[0051] The definition of the alloy skin layer containing Au and Pd of the above-mentioned bonding wire is explained. The boundary between the alloy skin layer containing Au and Pd and the Pd coating layer is determined based on the Au concentration. With the position where the Au concentration is 10 atomic % as the boundary, the area with an Au concentration of 10 atomic % or more is determined as the alloy skin layer containing Au and Pd, and the area with less than 10 atomic % is determined as the Pd coating layer. In addition, even if the Pd concentration is 50 atomic % or more, as long as Au exists at more than 10 atomic %, it is determined as the alloy skin layer containing Au and Pd. This is because if the Au concentration is in the above-mentioned concentration range, it can be expected that the structure of the Au skin layer will obtain an improvement in characteristics. The alloy skin layer containing Au and Pd is a region that is an Au-Pd alloy and contains Au and Pd and has a concentration gradient in the depth direction of the wire. The reason for forming the region with this concentration gradient in the alloy skin layer containing Au and Pd is that sometimes the heat treatment in the manufacturing process causes the diffusion of Au and Pd atoms. Furthermore, the alloy skin layer containing Au and Pd may contain unavoidable impurities and Cu.
[0052] In the bonding wire of the present invention, the alloy skin layer containing Au and Pd reacts with the Pd coating layer, which can improve the adhesion strength between the alloy skin layer containing Au and Pd, the Pd coating layer, and the Cu alloy core material, and inhibit the peeling of the Pd coating layer or the alloy skin layer containing Au and Pd during wedge bonding. As a result, the bonding wire of the present invention can further improve the wedge bonding. If the thickness of the alloy skin layer containing Au and Pd is less than 0.0005μm, the above effect cannot be fully obtained, and if it is thicker than 0.050μm, the FAB shape may be eccentric. From the viewpoint of obtaining good wedge bonding, the thickness of the alloy skin layer containing Au and Pd is preferably 0.0005μm or more, more preferably 0.001μm or more, 0.002μm or more, or 0.003μm or more. From the viewpoint of suppressing eccentricity and obtaining a good FAB shape, the thickness of the alloy skin layer comprising Au and Pd is preferably 0.050 μm or less, more preferably 0.045 μm or less, 0.040 μm or less, 0.035 μm or less, or 0.030 μm or less. In addition, the alloy skin layer comprising Au and Pd can be formed by the same method as the Pd coating layer.
[0053] The bonding wire of the present invention may also contain a total of 0.03 to 3% by mass of one or more of Al, Ga, Ge, and In (the third alloy element group). Therefore, it is preferred because the bonding reliability can be improved under the high temperature and high humidity environment of 130°C and 85% relative humidity, which is the HAST evaluation condition. It can be considered that if the Pd-coated Cu bonding wire contains the third alloy element group within the above content range, it has a tendency to further suppress the formation of Cu9Al4 intermetallic compounds in the bonding portion. During the FAB formation of the ball bonding portion, the third alloy element group in the wire also diffuses into the Pd coating layer. It is believed that the third alloy element group present in the Pd-rich layer at the interface between Cu and Al in the ball bonding portion further enhances the mutual diffusion suppression effect of Cu and Al brought by the Pd-rich layer, and as a result, suppresses the formation of Cu9Al4, which is easily corroded under high temperature and high humidity environments. In addition, the third alloy element group contained in the wire may also have the effect of directly inhibiting the formation of Cu9Al4. The total content of the third alloy element group is preferably 0.05 mass % or more, 0.1 mass % or more, 0.2 mass % or more, 0.3 mass % or more, 0.4 mass % or more, or 0.5 mass % or more.
[0054] Furthermore, when a ball portion is formed using a Pd-coated Cu bonding wire containing a predetermined amount of the third alloy element group and the FAB is observed using a scanning electron microscope (SEM), a plurality of nanostructured ... If the precipitates are analyzed by energy dispersive X-ray spectroscopy (EDS), it can be confirmed that the third alloy element group is enriched. Although the detailed mechanism is not clear, it is believed that the precipitates observed on the FAB exist at the bonding interface between the ball part and the electrode, which significantly improves the bonding reliability of the ball joint in a high temperature and high humidity environment of 130°C and 85% relative humidity.
[0055] On the other hand, from the perspective of obtaining a good FAB shape and suppressing the hardening of the bonding wire to obtain good wedge bonding properties, the concentration of the third alloy element group relative to the entire wire is a total of less than 3 mass%, preferably less than 2 mass%, and more preferably less than 1.5 mass%, or less than 1.2 mass%.
[0056] The bonding wire of the present invention may also contain a total of 0.1 to 1000 mass ppm (Sn ≦ 10 mass ppm, Bi ≦ 1 mass ppm) of one or more of As, Te, Sn, Bi, and Se (the fourth alloy element group). Therefore, it is preferred because it can improve the bonding reliability under the high temperature and high humidity environment of 130°C and 85% relative humidity as the HAST evaluation conditions. It can be considered that if the fourth alloy element group is contained within the above content range, there is a tendency to further suppress the formation of Cu9Al4 intermetallic compounds in the joint. If a specified amount of these elements is contained, the interfacial tension between the Cu of the core material and the Pd of the coating layer is reduced when the ball is formed, and the wettability of the interface is improved, so the Pd enrichment of the ball joint interface is more significantly manifested. Therefore, it can be inferred that in the high temperature and high humidity environment of the HAST evaluation conditions, the mutual diffusion inhibition effect of Cu and Al brought by the Pd-rich layer becomes stronger, and as a result, the amount of Cu9Al4 that is easily corroded under the action of Cl is reduced, and the bonding reliability of the ball joint in the high temperature and high humidity environment is significantly improved.
[0057] From the viewpoint of increasing the bonding life of the ball joint in a high temperature and high humidity environment of 130°C and 85% relative humidity and improving the bonding reliability, the concentration of the fourth alloy element group relative to the entire bonding wire is a total of 0.1 mass ppm or more, preferably 0.5 mass ppm or more, more preferably 1 mass ppm or more, and further preferably 1.5 mass ppm or more, 2 mass ppm or more, 2.5 mass ppm or more, or 3 mass ppm or more.
[0058] On the other hand, from the viewpoint of obtaining a good FAB shape and good ball bonding, the concentration of the fourth alloy element group in the wire is 1000 mass ppm or less in total, preferably 950 mass ppm or less, 900 mass ppm or less, 850 mass ppm or less, or 800 mass ppm or less. In addition, since the FAB shape becomes poor when the Sn concentration exceeds 10 mass ppm or the Bi concentration exceeds 1 mass ppm, it is preferred to make Sn ≦ 10 mass ppm and Bi ≦ 1 mass ppm, because the FAB shape can be further improved. Furthermore, it is more preferred to make the Se concentration 4.9 mass ppm or less, because the FAB shape and wedge bonding can be further improved.
[0059] The bonding wire of the present invention may further contain 0.1 to 200 mass ppm of one or more of B, P and La (fifth alloy element group). This is preferred because it can improve the crush shape of the ball joint required for high-density mounting, that is, improve the roundness of the ball joint shape.
[0060] In the case where the Pd-coated Cu bonding wire contains a prescribed amount of the first + alloy element group as in the present invention, if Cu is also present on the outermost surface of the bonding wire, there is a tendency to further suppress the generation of Cu9Al4 intermetallic compounds in the bonding portion. In this case, the interaction between the first + alloy element group and Cu contained in the bonding wire promotes the enrichment of Pd on the FAB surface when the FAB is formed, and the enrichment of Pd at the ball bonding interface is more significantly manifested. Therefore, it can be inferred that the mutual diffusion inhibition effect of Cu and Al brought by the Pd-enriched layer becomes stronger, the generation amount of Cu9Al4 that is easily corroded under the action of Cl is reduced, and the bonding reliability of the ball bonding portion in a high temperature and high humidity environment is further improved. Here, the outermost surface refers to the area on the surface of the bonding wire measured by an Auger electron spectroscopy device without sputtering or the like.
[0061] When Cu exists on the outermost surface of the Pd coating layer, if the concentration of Cu on the outermost surface is 35 atomic % or more, the sulfurization resistance of the wire surface is reduced, and the service life of the bonding wire is reduced, so it is sometimes not suitable for practical use. Therefore, when Cu exists on the outermost surface of the Pd coating layer, it is preferred that the concentration of Cu on the outermost surface is less than 35 atomic %. It is more preferred that the concentration of Cu on the outermost surface is less than 30 atomic %.
[0062] When the bonding wire contains the first to fifth alloying element groups, the effect of the present invention can be exerted by any of the methods of containing these elements in the Cu alloy core material and coating these elements on the Cu alloy core material or the surface of the wire. Because the addition amount of these components is trace, the addition method varies greatly. No matter which method is used to add, the effect is manifested as long as the components are included in the specified concentration range. Regarding Pd in the first + alloying element group, since it needs to be distinguished from the Pd coating layer of the bonding wire, it is specified based on the analysis value of the Pd content in the Cu alloy core material converted into the content in the bonding wire. That is, the Pd content can be calculated by analyzing the Pd content in the Cu alloy core material and multiplying the analysis value by "(the mass of the Cu alloy core material per unit length of the wire) / (the mass of the bonding wire per unit length of the wire)". The Pd in the Pd coating layer is not added to the Pd content.
[0063] In the concentration analysis of the Pd coating layer, the alloy skin layer containing Au and Pd, and the concentration analysis of Pd in the Cu alloy core material, a method of performing analysis while cutting from the surface of the bonding wire in the depth direction by sputtering or the like, or a method of exposing the wire section and performing line analysis, point analysis, etc. is effective. The analytical device used in these concentration analyses can be an Auger electron spectrometer equipped with a scanning electron microscope or a transmission electron microscope, an energy dispersive X-ray analyzer, an electron beam microanalyzer, etc. As a method for exposing the wire section, mechanical grinding, ion etching, etc. can be used. For example, in the case where the Cu alloy core material contains a region with a concentration gradient of Pd, the cross section of the bonding wire is subjected to line analysis and point analysis, and the concentration analysis is performed on the region (for example, the central part of the wire section (the range of the diameter of 1 / 4 of the wire diameter)) that does not have a concentration gradient of Pd in the cross section of the Cu alloy core material. Trace analysis of the first to fifth alloying element groups other than Pd in the bonding wire can be performed by analyzing a liquid obtained by dissolving the bonding wire with a strong acid using an ICP emission spectrometer or an ICP mass spectrometer to detect the concentration of elements contained in the entire bonding wire.
[0064] (Manufacturing method)
[0065] Next, a method for manufacturing a bonding wire according to an embodiment of the present invention is described. After manufacturing the Cu alloy used for the core material, the bonding wire is obtained by thinning it into a wire shape, forming a Pd coating layer and an Au layer, and performing a heat treatment. Sometimes, after forming the Pd coating layer and the Au layer, wire drawing and heat treatment are performed again. The method for manufacturing the Cu alloy core material, the method for forming the Pd coating layer, the alloy skin layer containing Au and Pd, and the heat treatment method are described in detail.
[0066] The Cu alloy used for the core material is obtained by dissolving Cu as a raw material and the element to be added together and solidifying it. When dissolving, an arc heating furnace, a high-frequency heating furnace, a resistance heating furnace, etc. can be used. In order to prevent the mixing of gases such as O2 and H2 from the atmosphere, it is preferably dissolved in a vacuum atmosphere or an inactive atmosphere such as Ar and N2.
[0067] The method of forming Pd coating layer and Au layer on the surface of Cu alloy core material has plating method, evaporation method, melting method etc. Plating method can apply any one of electrolytic plating method and electroless plating method. In the case of electrolytic plating called strike plating and flash plating, its plating speed is fast, and the closeness with substrate is also good. The solution used for electroless plating is classified into substitution type and reduction type, and it is sufficient to use only substitution type plating when thickness is thin, but it is effective to implement reduction type plating in stages after substitution type plating when thickness is thicker.
[0068] Among the vapor deposition methods, physical adsorption such as sputtering, ion plating, and vacuum vapor deposition, and chemical adsorption such as plasma CVD can be used. These are all dry methods, and do not require cleaning after the formation of the Pd coating layer and the Au layer, and there is no need to worry about surface contamination during cleaning.
[0069] By performing heat treatment after the Pd coating layer and the Au layer are formed, the Pd in the Pd coating layer diffuses into the Au layer to form an alloy skin layer containing Au and Pd. Instead of forming the alloy skin layer containing Au and Pd by heat treatment after the Au layer is formed, the alloy skin layer containing Au and Pd may be coated from the beginning.
[0070] For the formation of Pd coating, alloy skin layer including Au and Pd, the method of forming these layers after drawing to the final wire diameter and the method of repeatedly drawing to the target wire diameter after forming these layers on the thick diameter Cu alloy core are effective. In the case of the former forming the Pd coating with the final diameter, the alloy skin layer including Au and Pd, manufacturing, quality management, etc. are simple. In the case of the latter combining the Pd coating, the alloy skin layer including Au and Pd with drawing, it is advantageous to improve the adhesion with the Cu alloy core. As a specific example of each formation method, a method of forming a Pd coating, an alloy skin layer including Au and Pd on the Cu alloy core of the final wire diameter while continuously sweeping the wire in the electrolytic plating solution can be cited, or after the thick Cu alloy core is immersed in an electrolytic or electroless plating bath to form a Pd coating, an alloy skin layer including Au and Pd, the lead is drawn to reach the method of the final wire diameter, etc.
[0071] After forming the Pd coating layer, the alloy skin layer comprising Au and Pd, sometimes heat treatment is performed. By heat treatment, atoms diffuse between the alloy skin layer comprising Au and Pd, the Pd coating layer, and the Cu alloy core material and the adhesion strength is improved, so it is effective to suppress the peeling of the alloy skin layer comprising Au and Pd or the Pd coating layer in the processing and improve productivity. In order to prevent the mixing from O2 in the atmosphere, it is preferably heat treated in an inactive atmosphere such as vacuum atmosphere or Ar, N2.
[0072] As described above, by adjusting the conditions of the diffusion heat treatment or annealing heat treatment applied to the bonding wire, the Cu of the core material diffuses in the Pd coating layer or the alloy skin layer containing Au and Pd, so that Cu can reach the outermost surface of the bonding wire and exist on the outermost surface. As a heat treatment for causing Cu to exist on the outermost surface, as described above, a heat treatment for forming an alloy skin layer containing Au and Pd can be used. When performing a heat treatment for forming an alloy skin layer, by selecting the heat treatment temperature and time, Cu can be present on the outermost surface or not. Furthermore, the Cu concentration on the outermost surface can also be adjusted to a specified range (for example, a range of 1 to 50 atomic %). Cu can also be diffused to the outermost surface by a heat treatment other than when the alloy skin layer is formed.
[0073] As described above, when the bonding wire contains the first to fifth alloy element groups, the effects of the present invention can be exhibited by either a method of containing these elements in the Cu alloy core material or a method of containing these elements by coating the Cu alloy core material or the wire surface.
[0074] As a method of adding the above-mentioned components, the simplest method is to add them in advance to the starting material of the Cu alloy core material. For example, after weighing high-purity copper and the above-mentioned raw materials of the component elements as starting materials, they are heated and melted under high vacuum or in an inert atmosphere such as nitrogen and argon to make an ingot to which the above-mentioned components are added in a target concentration range, as a starting material containing the above-mentioned component elements at a target concentration. Therefore, in a preferred embodiment, the Cu alloy core material of the bonding wire of the present invention contains the elements in a manner such that the concentrations of the elements of the first to fifth alloying element groups relative to the entire wire are respectively at a predetermined concentration. The preferred numerical range of the total concentration is as described above.
[0075] The above-mentioned components can also be contained by coating the surface of the online manufacturing process during the online manufacturing process. In this case, it can be assembled somewhere in the online manufacturing process, or it can be repeated multiple times. It can also be assembled in multiple processes. It can be added to the Cu surface before Pd coating, it can also be added to the Pd surface after Pd coating, it can also be added to the Au surface after Au coating, and it can also be assembled in each coating process. As a coating method, it can be from an aqueous solution Choose from plating (wet) and evaporation (dry).
[0076] [Example]
[0077] Hereinafter, the bonding wire according to the embodiment of the present invention will be described in detail with reference to Examples.
[0078] (sample)
[0079] First, the method for making the sample is described. For Cu as the raw material of the core material, Cu with a purity of 99.99% by mass or more and the remainder consisting of inevitable impurities is used. For the first to fifth alloy element groups, elements with a purity of 99% by mass or more and the remainder consisting of inevitable impurities are used. In order to make the composition of the wire or core material the target composition, the first to fifth alloy element groups are formulated as additive elements to the core material. Regarding the addition of the first to fifth alloy element groups, monomers can be formulated, but in the case of high melting point elements or extremely small amounts of additives in the monomer form, a Cu master alloy containing the additive elements can also be prepared in advance and formulated to the target additive amount.
[0080] For the core material Cu alloy, the raw material is charged into a tube with a diameter of The obtained carbon is heated to 1090-1300°C in a high frequency furnace in a vacuum or in an inert atmosphere such as N2 or Ar gas to dissolve the carbon, and then cooled in the furnace. The alloy is drawn and processed into After that, the wire drawing process is continuously performed using a die to produce Wire. A commercially available lubricant is used in the wire drawing, and the wire drawing speed is 20 to 150 m / min. After pickling with hydrochloric acid to remove the oxide film on the surface of the wire, a Pd coating layer of 1 to 15 μm is formed in a manner that covers the entire surface of the Cu alloy of the core material. Furthermore, for some of the wires, a 0.05 to 1.5 μm alloy skin layer containing Au and Pd is formed on the Pd coating layer. Electrolytic plating is used to form the Pd coating layer and the alloy skin layer containing Au and Pd. A commercially available semiconductor plating solution is used as the plating solution. After that, it is processed to a diameter of 20 μm by repeatedly performing heat treatment at 200 to 500°C and wire drawing. After processing, heat treatment is performed while flowing N2 or Ar gas, so that the final elongation at break reaches about 5 to 15%. The heat treatment method is to continuously sweep the lead while flowing N2 or Ar gas. The feed speed of the lead wire is 20 to 200 m / min, the heat treatment temperature is 200 to 600° C., and the heat treatment time is 0.2 to 1.0 second.
[0081] For the concentration analysis of the Pd coating layer and the alloy skin layer containing Au and Pd, the analysis was performed using an Auger electron spectrometer while sputtering with Ar ions from the surface of the bonding wire to the depth direction. The thickness of the coating layer and the alloy skin layer was obtained based on the concentration distribution in the depth direction (the unit of depth is SiO2 conversion). The area where the concentration of Pd is 50 atomic % or more and the concentration of Au is less than 10 atomic % is regarded as the Pd coating layer, and the area where the Au concentration on the surface of the Pd coating layer is 10 atomic % or more is regarded as the alloy skin layer. The thickness and composition of the coating layer and the alloy skin layer are respectively recorded in Tables 1 to 6. For the concentration of Pd in the Cu alloy core material, the line section is exposed, and the center of the line section (the diameter range of 1 / 4 of the line diameter) is analyzed by line analysis, point analysis, etc. using an electron beam microanalyzer equipped with a scanning electron microscope. As a method for exposing the line section, mechanical grinding, ion etching, etc. are used. The Pd content in the bonding wire is calculated by multiplying the Pd content analysis value in the Cu alloy core material analyzed above by "(Cu alloy core material mass per wire unit length) / (bonding wire mass per wire unit length)". The concentrations of the first to fifth alloy element groups other than Pd in the bonding wire are detected as the concentrations of the elements contained in the entire bonding wire by analyzing the liquid obtained by dissolving the bonding wire with a strong acid using an ICP emission chromatograph and an ICP mass spectrometer.
[0082] (Evaluation method)
[0083] Regarding the bonding reliability of ball joints in high temperature and high humidity environments or high temperature environments, samples for bonding reliability evaluation were prepared, and HAST and HTS evaluations were performed. The bonding life of the ball joints in each test was determined. For the samples for bonding reliability evaluation, ball bonding was performed using a commercially available wire bonding machine with electrodes formed by forming a 0.8μm thick Al-1.0%Si-0.5%Cu alloy film on a Si substrate on a general metal frame. Balls of size 1000 mm were formed while N2+5%H2 gas was allowed to flow at a flow rate of 0.4 to 0.6 L / min. range. After the bonding wires were bonded, the samples were sealed using two epoxy resins with different sulfur contents. As a low-concentration sulfur-containing resin, a resin with a sulfur content of 2 mass ppm was used, and as a high-concentration sulfur-containing resin, a resin with a sulfur content of 16 mass ppm was used. For the evaluation of the sulfur content in the epoxy resin, the resin was crushed and heated at 200°C for 10 hours in a nitrogen flow, and the outgassing (outgas) from the resin contained in the carrier nitrogen was captured with hydrogen peroxide water, and the sulfur content was evaluated by ion chromatography.
[0084] For HAST evaluation, the samples prepared for joint reliability evaluation were exposed to a high temperature and high humidity environment of 130°C and 85% relative humidity using an unsaturated pressure cooker tester, and a bias of 7 V was applied. For the joint life of the ball joint, a shear test of the ball joint was performed every 48 hours, and the time when the shear strength value became 1 / 2 of the shear strength obtained at the initial stage was taken as the joint life of the ball joint. The shear test after the high temperature and high humidity test was performed after the resin was removed by acid treatment to expose the ball joint.
[0085] The shear tester for HAST evaluation uses a tester manufactured by DAGE. The shear strength value uses the average value of the measured values of 10 randomly selected ball joints. In the above evaluation, if the joint life is less than 96 hours, it is judged to have practical problems, marked with an × symbol, if it is more than 96 hours and less than 144 hours, it is considered to be practical but slightly problematic, marked with a △ symbol, if it is more than 144 hours and less than 288 hours, it is judged to have no practical problems, marked with an ○ symbol, if it is more than 288 hours and less than 384 hours, it is judged to be excellent, marked with a ◎ symbol, and if it is more than 384 hours, it is judged to be particularly excellent, marked with a ◎◎ symbol, and recorded in the "HAST" column of Tables 1 to 6.
[0086] For HTS evaluation, the prepared samples for joint reliability evaluation were exposed to a high temperature environment of 200°C using a high temperature thermostat. For the joint life of the ball joint, a shear test of the ball joint was performed every 500 hours, and the time when the shear strength value became 1 / 2 of the shear strength obtained at the initial stage was taken as the joint life of the ball joint. The shear test after the high temperature test was performed after the resin was removed by acid treatment to expose the ball joint.
[0087] The shear tester for HTS evaluation uses a tester manufactured by DAGE. The shear strength value uses the average value of the measured values at 10 randomly selected ball joints. In the above evaluation, if the joint life is less than 250 hours, it is judged to have practical problems, marked with an × symbol, if it is more than 250 hours and less than 500 hours, it is considered that although it can be practical, there is a need for improvement, marked with a △ symbol, if it is more than 500 hours and less than 1000 hours, it is judged to have no practical problems, marked with a ○ symbol, if it is more than 1000 hours and less than 2000 hours, it is judged to be excellent, marked with a ◎ symbol, if it is more than 2000 hours and less than 3000 hours, it is judged to be particularly excellent, marked with a ◎◎ symbol, and recorded in the "HTS" column of Tables 1 to 6.
[0088] For the evaluation of ball formation (FAB shape), the ball before bonding was selected for observation, and the presence or absence of bubbles on the surface of the ball and the presence or absence of deformation of the originally positive sphere were determined. If any of the above occurs, it is judged to be defective. In order to suppress oxidation in the melting process, N2 gas is blown at a flow rate of 0.5L / min while forming the ball. The size of the ball is 34μm. 50 balls were observed for 1 condition. SEM was used for observation. In the evaluation of ball formation, if more than 5 defects occur, it is judged to have a problem, marked with an × symbol. If there are 3 to 4 defects, it is considered that although it can be practical, there are slight problems, marked with a △ symbol. If there are 1 to 2 defects, it is judged to be no problem, marked with an ○ symbol. If no defects occur, it is judged to be excellent, marked with a ◎ symbol, and recorded in the "FAB shape" column of Tables 1 to 6.
[0089] For the evaluation of the wedge bonding in the wire bonding part, 1000 leads of the lead frame were bonded and the frequency of peeling of the bonding part was judged. The lead frame used a Fe-42 atomic % Ni alloy lead frame with 1 to 3 μm Ag plating. In this evaluation, stricter bonding conditions than usual were assumed, and the soldering station temperature was set to 150°C, which is lower than the general set temperature range. In the above evaluation, if more than 11 defects occur, it is judged that there is a problem, marked with an × symbol. If the number of defects is 6 to 10, it is considered that it is practical but there are slight problems, marked with a △ symbol. If the number of defects is 1 to 5, it is judged that there is no problem, marked with an ○ symbol. If no defects occur, it is judged to be excellent, marked with a ◎ symbol, and recorded in the "Wedge Bonding" column of Tables 1 to 6.
[0090] For the evaluation of the crush shape of the ball joint, the ball joint after the joint was observed from directly above and judged based on its roundness. The joining object used an electrode of an Al-0.5% Cu alloy with a thickness of 0.1μm formed on a Si substrate. An optical microscope was used for observation, and 200 places were observed for one condition. The crush shape of the ball joint was judged to be poor as an elliptical shape with a large deviation from the perfect circle and a shape with anisotropy in deformation. In the above evaluation, if more than 6 defects are generated, it is judged to have a problem and marked with an × symbol. If there are 4 to 5 defects, it is considered that although it can be practical, there are slight problems and marked with a △ symbol. If there are 1 to 3 defects, it is judged to be no problem and marked with a ○ symbol. If all good roundness is obtained, it is judged to be particularly excellent and marked with a ◎ symbol. It is recorded in the "Crush Shape" column of Tables 1 to 6.
[0091] In the evaluation of chip damage, 200 ball welds were performed on an electrode of an Al-0.5% Cu alloy with a thickness of 1.0 μm formed on a Si substrate, and the wire and the Al electrode were dissolved with a liquid solution to expose the Si substrate. The evaluation was performed by observing whether damage occurred on the Si substrate. If two or more damages occurred, it was judged as bad and marked with an × symbol. If there was only one damage, it was considered to be no problem and marked with an ○ symbol. If no damage was observed, it was considered good and marked with a ◎ symbol. It was recorded in the "Chip Damage" column of Tables 1 to 6. ○ and ◎ are qualified.
[0092] [Table 1-1]
[0093]
[0094] [Table 1-2]
[0095]
[0096] [Table 1-3]
[0097]
[0098] [Table 2-1]
[0099]
[0100] [Table 2-2]
[0101]
[0102] [Table 2-3]
[0103]
[0104] [Table 3-1]
[0105]
[0106] [Table 3-2]
[0107]
[0108] [Table 3-3]
[0109]
[0110] [Table 4-1]
[0111]
[0112] [Table 4-2]
[0113]
[0114] [Table 4-3]
[0115]
[0116] [Table 5-1]
[0117]
[0118] [Table 5-2]
[0119]
[0120] [Table 5-3]
[0121]
[0122] [Table 6-1]
[0123]
[0124] [Table 6-2]
[0125]
[0126] [Table 6-3]
[0127]
[0128] The results are shown in Tables 1-1 to 6-3. Inventive Examples No. 1 to 127 in Tables 1-1 to 5-3 are inventive examples, and Comparative Examples No. 1 to 15 in Tables 6-1 to 6-3 are comparative examples. Numerical values outside the range of the present invention are underlined.
[0129] The present invention examples No. 1 to 127 in Tables 1-1 to 5-3 are bonding wires for semiconductor devices having a Cu alloy core material and a Pd coating layer formed on the surface of the Cu alloy core material. The component composition of the wire is within the scope of the present invention, and good results can be obtained in all evaluation items including HAST results, HST results (either low-concentration sulfur-containing resin or high-concentration sulfur-containing resin), FAB shape, wedge bondability, crushing shape of the ball joint, and chip damage.
[0130] Comparative Examples No. 1 to 15 in Tables 6-1 to 6-3 are described below. The contents of the first + alloying element group in Comparative Examples Nos. 1 to 5 and 12 were outside the lower limit of the present invention, and both HAST and HTS (including low-concentration sulfur-containing resin) were poor.
[0131] The contents of the first alloy element group and the second alloy element group of Comparative Examples No. 6 to 8 and 11 are within the scope of the present invention, but the content of the second alloy element group is outside the lower limit of the scope of the present invention. Comparative Example No. 9 contains Zn and the total content of the first alloy element group and Zn is outside the scope of the present invention. The HTS results using high-concentration sulfur-containing resins are all poor.
[0132] In Comparative Examples Nos. 10 and 13 to 15, the content of any one of the first alloy element group and the second alloy element group exceeded the upper limit of the range of the present invention, and the chip damage was unacceptable.
Claims
1. A bonding wire for a semiconductor device, comprising a Cu alloy core material and a Pd coating layer formed on a surface of the Cu alloy core material, characterized in that: The bonding wire contains one or more of Ni, Rh, and Ir as "a first alloying element group" and one or both of Pd: 0.05 mass % or more, and when the content of the first alloying element group is evaluated as the content in the bonding wire and the Pd content is evaluated by converting the content of the first alloying element group into the content in the bonding wire based on the Pd content in the Cu alloy core material, the total content of the first alloying element group and Pd in the evaluated content is 0.03 to 2 mass %; The bonding wire further contains one or more of Li, Sb, Cr, Co, Sc, and Y as a second alloy element group. When the bonding wire does not contain Sb, the total content of the second alloy element group is 0.002 to 3 mass %, and when the bonding wire contains Sb, the total content of the second alloy element group is 0.015 to 3 mass %.
2. The bonding wire for a semiconductor device according to claim 1, wherein The bonding wire further contains one or more of Ca, Mg and Zn, Satisfy at least one of the following conditions (1) to (3): Condition (1): The Ca content in the bonding wire is 0.011 mass % or more; Condition (2): The content of Mg in the bonding wire is 0.011 mass % or more; Condition (3): The total content of the first alloy element group and Zn in the bonding wire is 2.1 mass % or more.
3. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: Among the contents evaluated above, the total content of the first alloy element group and Pd is 0.05 mass % or more.
4. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: Among the contents evaluated, the total content of the first alloy element group and Pd is 0.1 mass % or more.
5. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: Among the contents evaluated above, the content of Pd was 0.1 mass % or more.
6. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: Among the contents evaluated, the total content of the first alloy element group and Pd is 1.8 mass % or less.
7. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire contains 0.05 mass % or more of one or more of Li, Sb, Cr, Co, Sc, and Y in total.
8. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire contains 2.5 mass % or less of one or more of Li, Sb, Cr, Co, Sc, and Y in total.
9. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The Sb content in the bonding wire is 0.05 mass % or more.
10. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire further contains Fe, and the content of Fe in the bonding wire is 0.015 mass % or more.
11. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire further contains Fe, and the content of Fe in the bonding wire is 0.05 mass % or more.
12. The bonding wire for a semiconductor device according to claim 2, wherein: The total content of the first alloy element group and Zn in the bonding wire is 2.5 mass % or more.
13. The bonding wire for a semiconductor device according to claim 2, wherein: The total content of the first alloy element group and Zn in the bonding wire is 3.6 mass % or less.
14. The bonding wire for a semiconductor device according to claim 2, wherein: The content of Zn in the bonding wire is 0.3 mass % or more.
15. The bonding wire for a semiconductor device according to claim 2, wherein: The Ca content in the bonding wire is 0.05 mass % or more.
16. The bonding wire for a semiconductor device according to claim 2, wherein: The content of Mg in the bonding wire is 0.05 mass % or more.
17. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire contains at least one of Li, Cr, Sc, and Y in an amount of 0.05 mass % or more in total.
18. The bonding wire for a semiconductor device according to claim 17, wherein The bonding wire contains 0.08 mass % or more of Y.
19. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The total content of Sc and Y in the bonding wire is 2.5 mass % or less.
20. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The thickness of the Pd coating layer is 0.015 to 0.150 μm.
21. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The Pd coating layer has a thickness of 0.02 μm or more.
22. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The thickness of the Pd coating layer is 0.03 μm or more.
23. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The thickness of the Pd coating layer is 0.100 μm or less.
24. The bonding wire for a semiconductor device according to claim 3, wherein An alloy skin layer containing Au and Pd is further provided on the Pd coating layer.
25. The bonding wire for a semiconductor device according to claim 24, wherein The thickness of the alloy skin layer containing Au and Pd is 0.050 μm or less.
26. The bonding wire for a semiconductor device according to claim 25, wherein The thickness of the alloy skin layer containing Au and Pd is greater than 0.001 μm.
27. The bonding wire for a semiconductor device according to claim 25, wherein The thickness of the alloy skin layer containing Au and Pd is greater than 0.002 μm.
28. The bonding wire for a semiconductor device according to claim 25, wherein The thickness of the alloy skin layer containing Au and Pd is 0.030 μm or less.
29. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire further contains 0.03 to 3 mass % in total of one or more of Al, Ga, Ge, and In.
30. The bonding wire for a semiconductor device according to claim 29, wherein The total content of one or more of Al, Ga, Ge, and In in the bonding wire is 0.05 mass % or more.
31. The bonding wire for a semiconductor device according to claim 29, wherein The total content of one or more of Al, Ga, Ge, and In in the bonding wire is 0.1 mass % or more.
32. The bonding wire for a semiconductor device according to claim 29, wherein The total content of one or more of Al, Ga, Ge, and In in the bonding wire is 2 mass % or less.
33. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire further contains 0.1 to 1000 mass ppm in total of one or more of As, Te, Sn, Bi, and Se, wherein Sn≦10 mass ppm and Bi≦1 mass ppm.
34. The bonding wire for a semiconductor device according to claim 33, wherein The total content of one or more of As, Te, Sn, Bi, and Se in the bonding wire is 0.5 mass ppm or more.
35. The bonding wire for a semiconductor device according to claim 33, wherein The total content of one or more of As, Te, Sn, Bi, and Se in the bonding wire is 1 mass ppm or more.
36. The bonding wire for a semiconductor device according to claim 33, wherein The total content of one or more of As, Te, Sn, Bi, and Se in the bonding wire is 800 mass ppm or less.
37. The bonding wire for a semiconductor device according to claim 33, wherein The concentration of Se in the bonding wire is 4.9 mass ppm or less.
38. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: The bonding wire further contains one or more of B, P, and La in an amount of 0.1 to 200 mass ppm in total.
39. The bonding wire for a semiconductor device according to claim 1 or 2, wherein: Cu exists on the outermost surface of the bonding wire.
40. The bonding wire for a semiconductor device according to claim 39, wherein The Cu concentration on the outermost surface of the bonding wire is less than 35 atomic %.